Investigating the Impact of Ageing on the Morphological Characteristics of Rejuvenated Asphalt Binder - Muhammad Ibrahim Khalili Abd Rahim,; Haryati Yaacob,; Mohd Rosli Hainin,; Mohd Khairul Afzan Mohd Lazi,; Muhammad Naqiuddin Mohd Warid,; Norzita Ngadi,; Ekarizan Shaffie,; Mohamad Ikhwan Jamaludin, (International Journal of Integrated Engineering, 2025)
The performance and longevity of asphalt pavement are greatly impacted by aging. However, after a several years of services, asphalt pavement become harder and looses its flexibility, impact comfort and safety for road users. To overcome this problems asphalt pavement required an effective maintenance or repair. The utilization of rejuvenator in aged asphalt is one of popular rehabilitation technique. The aim of this study is to discover the impact of aging and rejuvenation; waste cooking oil (WCO) to the asphalt binder’s morphological changes by utilized contact angle and Atomic Force Microscopy (AFM) analysis. To evaluate the morphological changes in asphalt binder, this study employed a Sessile drop method and tapping mode. Asphalt binders were also subjected to short-term and long-term aging simulation. The result shows WCO effectively increase the Surface Free Energy (SFE) value and reduced the surface roughness of asphalt binder. The result also illustrates, as the aging duration increases, the contact angle tangent slope between asphalt binder and test liquids were increased, indicating a reduction in SFE value of asphalt binder. From AFM images, the size of bee structure or catana phase are increased as the aging duration increase, indicating a morphological change and increase in surface roughness. This phenomenon can be attribute to changes in asphaltenes contents of asphalt binder due to aging and rejuvenation process. These findings will provide an important information about effect of aging and rejuvenation process on the asphalt binder’s surface morphology.